Effect of Work Discipline and The Work Environment on Employee Performance CV. Bolon Tua - Simbolon, Sardo Arifin Bintang; Oktafien, Shinta (Technium Social Sciences Journal, 2021)
CV. Bolon Tua is a company engaged in oil palm. 2015-2019 each month experienced inconsistent or fluctuating productivity with a monthly average decreasing from 2015-2019. indicated that the performance of the employees of CV. Bolon Tua as a whole has decreased. This study aims to determine and analyze the effect of work discipline and work environment on employee performance at CV. Bolon Tua. The research method used is descriptive and verification research methods, with a sample of 60 respondents. Methods of data analysis using multiple linear regression analysis and hypothesis testing. The research results obtained are CV. Bolon Tua still has poor work discipline. CV. Bolon Tua already has a conducive physical and non-physical work environment that makes employees comfortable at work. Employee performance owned by CV. Bolon Tua is considered high enough, although it still needs to be improved. Employee performance is influenced by work discipline in a positive and significant way. Employee performance is influenced positively and significantly by the work environment. Employee performance is positively and significantly influenced by work discipline and the work environment. The biggest influence is work discipline and the smallest influence is the work environment